Analis Kesalahan Berbahasa dalam Komentar Pengguna Akun tiktok Vina Mulyana Kajian sosiolinguistik - Khairunnisa Purba; Yulia Arfianty (At-Tadris: Journal of Islamic Education, 2025)
The content available on the TikTok application is increasingly diverse from educational content, comedy, vlogs, to personal experiences of its users. On TikTok, the content is free to explore and can be used anytime and anywhere. As a result, "content creators" can explore many things and are not tied to a particular topic or theme that they want to share on social media and do not require a lot of equipment or special locations to create content. Based on the Background of the Problem above, it encourages the author to what has been put forward, it can be concluded, identified several problems, namely What are the forms of language errors found in the comments and reflect the social orientation of the @Vina Muliana TikTok account and also What are the social factors that influence the occurrence of language errors in the @Vina Muliana TikTok account. This research design uses a qualitative approach. According to Sugiyono (in Desniarti et al., 2021), a qualitative research method is a method used to examine the condition of a natural object where the researcher is the key instrument. Qualitative data analysis techniques according to Sugiyono (2018: 335) are inductive, namely an analysis based on the data obtained, then a certain relationship pattern is developed or becomes a hypothesis, then based on this hypothesis, data is searched again repeatedly until it can be concluded whether the hypothesis can be accepted or rejected. The data collection for this study used a documentation technique in the form of screenshots on Vina Muliana's Tiktok account which contained an error in the comments on her description upload. In the TikTok social media comment column, netizens' statements were found to contain violations of politeness. And not all social media users understand and comprehend the situation regarding the importance of politeness. There are some people who do not know the rules of politeness when commenting. In addition, some people also find it difficult to leave old habits obtained from everyday language culture, attitudes and characters, so that these habits are carried over to written communication through the TikTok social media comment column. This certainly provides an indication that TikTok social media users as a social media that is currently popular are not accompanied by good, correct and polite language attitudes that will help speakers in building a smooth communication situation with their conversation partners.